BRAFV600E/pTERT double mutated papillary thyroid cancers exhibit immune gene suppression - Sigarteu Chindris, Ana-Maria; Rivera, Michael; Ma, Yaohua; Nair, Asha; Liu, Yi; Wang, Xue; Necela, Brian M.; Kachergus, Jennifer M.; Casler, John D.; Brett, Christopher; Rivas Mejia, Ana M.; Bernet, Victor J.; et al. (Frontiers in Endocrinology, 2024)
Introduction BRAFV600E mutation (BRAFmut) is common in papillary thyroid cancer (PTC), and most patients have an excellent outcome. However, a TERT-promoter mutation (pTERTmut) in the presence of BRAFmut (BRAFmutpTERTmut) has been demonstrated to confer a more aggressive behavior to PTC. Lymphocytic infiltration is often present in PTC. In this study, we sought to decipher the relationship between the BRAF and pTERT mutations and immune gene dysregulation in tumor samples from a cohort of 147 samples of PTC. Methods The abundance of 770 immune gene transcripts was determined by multiprex capture/detection and digital counting of mRNA transcripts using the NanoString nCounter® PanCancer Immune Profiling Panel. Results We identified 40 immune transcripts differentially expressed in BRAFmutpTERTmutvs BRAFmutpTERT wildtype (pTERTwt) (P<0.05). Transcripts induced by BRAFmut alone were significantly repressed in BRAFmutpTERTmut samples, such as genes expressed by lymphoid cells, antigen-presenting cells, and cytotoxic cells, including chemokines, cytokines, checkpoint control proteins, interferon downstream markers, TNF superfamily proteins and BMP markers. A validation analysis using 444 samples from The Cancer Genome Atlas (TCGA) PTC dataset yielded similar results. Deconvolution analysis confirmed differences in the immune cell populations such as increased presence of M2 macrophages in the BRAFmutpTERTmut Mayo cohort and a lower abundance of M1 macrophages in the BRAFmutpTERTmut TCGA cohort compared to BRAFmutpTERTwt. Most of the immune gene pathways were enriched in the BRAFmutpTERTwt tumors in both Mayo and TCGA cohorts but not in BRAFmutpTERTmut. BRAFmutpTERTwt had higher stromal lymphocytes infiltration as compared to BRAFwtpTERTwt tumors, corroborating the transcriptomic findings. Discussion To our knowledge this is the first report of a potential link between TERT and the immune microenvironment, offering an explanation for the aggressive nature of BRAFmutpTERTmut PTC.